(untitled) - Loewe, Michael (London, 1968)
This book introduce the historical and geographical context, the emperor and his goverment, the officials, social distinctions and occupations...
Keywords: China,China,Trung Quốc,Trung Quốc; Social life and customs,History,Phong tục và đời sống xã hội,Lịch sử; Han dynasty, 202 B.C.-220 A.D.,Triều đại nhà Hán, 202 B.C.-220 A.D.